Transanal endoscopic local resection versus radical excision in the treatment of massive rectal gastrointestinal stromal tumors: striving for therapeutic advantages - Taixuan Wan; Jingkun Xiao; Xingwei Zhang; Yunxing Shi; Hao Xie; Fujin Ye; Haoqi Zheng; Yihang Zhou; Zhanzheng Liu; Liang Kang; Liang Huang (Therapeutic Advances in Gastroenterology)
Objectives: To compare the therapeutic advantages of transanal endoscopic local resection (taLR) and transabdominal radical resection (tbRR) in the treatment of massive gastrointestinal stromal tumors (GIST). Design: Single-center retrospective study. Methods: From October 2012 to October 2022, the clinical, surgical, pathological, and prognostic data of patients with rectal GIST who underwent surgery were retrospectively collected. The patients were divided into the taLR group and the tbRR group according to the surgical methods, and the research indicators were compared. Results: Thirty-five patients with rectal GIST larger than 5 cm were enrolled, including 17 cases in the taLR group and 18 cases in the tbRR group. The taLR group showed shorter intraoperative time ( p  = 0.006), shorter postoperative hospital days ( p  = 0.035), earlier postoperative drainage tube removal ( p  = 0.007), and a higher anus preservation rate ( p  = 0.011). There was no significant survival difference in the 5-year disease-free survival between the taLR group and the tbRR group (94.1% vs 100%, p  = 0.405). Conclusion: In conclusion, there were no significant differences in survival between taLR and laparoscopic radical resection for massive rectal GIST. Moreover, compared with transabdominal radical excision technique, the transanal endoscopy surgery provides a new method of anal preservation, thereby improving the patient’s quality of life.